The Effects of Employee Retention on Company Performance Results: the Mediating Role of HRM Outcomes in Central European Headquarters of MNCs - Łukasz Haromszeki (Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu)
Aim: The main goal of the article was to determine the mediating role of HRM outcomes in the relationships between employee retention (ER) and company performance results (CPR), and to establish the existence of any identifiable regularities in this scope in the pre-pandemic and pandemic period of COVID-19 (understood as a crisis condition) in the headquarters (HQs) of multinational companies (MNCs).